1, 4NQ-BC enhances the lung inflammation by mediating the secretion of IL-33 which derived from macrophages. (October 2020) - Xiao, Qianqian; Song, Yiming; Chu, Hongqian; Tang, Mengmeng; Jiang, Jianjun; Meng, Qinghe; Hao, Weidong; Wei, Xuetao
Abstract: Black carbon (BC) is a product of incomplete combustion of fossil fuels and vegetation. The compelling evidence has demonstrated that it has a close relationship with several respiratory and cardiovascular diseases. BC provides the reactive sites and surfaces to absorb various chemicals, such as polycyclic aromatic hydrocarbons (PAH). Naphthoquinone is a typical PAHs which was found in particulate matter (PM) and 1, 4NQ-BC owned high oxidative potential and cytotoxicity. IL-33 is an alarmin which increases innate immunity through Th2 responses. It was reported that IL-33 was a potent inducer of pro-inflammatory cytokines, like IL-6. In our previous study, it was revealed that 1, 4NQ-BC instilled intratracheally to mice could trigger the lung inflammation and stimulate the secretion of IL-33 in lung tissue. We found that IL-33 could induce inflammation in lung itself. When the macrophages were eliminated, the secretion of IL-33 was reduced and the pathological damage in the lung was relieved after exposure to 1, 4NQ-BC. Both MAPK and PI3K/AKT signal pathways were involved in the process of IL-33 secretion and the lung inflammation induced by 1, 4NQ-BC. The findings herein support the notion that after exposure to 1, 4NQ-BC, the increased secretion of IL-33 was mainly derived from macrophages through both MAPK and PI3K/AKT signal pathways. Graphical abstract: Image 1 Highlights: IL-33 can induce lung inflammation itself. IL-33 plays a key role in the progress which 1, 4NQ-BC triggered lung inflammation. IL-33 may derive from macrophages after 1, 4NQ-BC treatment. MAPK and PI3K/AKT pathways are involved in the lung inflammation not only mediated by IL-33, but also 1, 4NQ-BC.